Nothing is as practical as a good theory! A systematic review of physical literacy interventions - Carl, Johannes; Barratt, Jaime; St. John, Laura; Töpfer, Clemens; Cairney, John; Pfeifer, Klaus (Ontario Physical Literacy Summit, 2021)
UNESCO (2015) and the World Health Organization (2018) embrace physical literacy as an important facet of quality physical education and promotion of lifelong physical activity. However, translating the theoretical-philosophical foundations of PL into practical interventions remains a significant challenge. Therefore, it is crucial to analyze how PL intervention studies recognize the holistic nature of PL and target PL domains. Our objective of this review was to examine how intervention studies acknowledge the theoretical assumptions of PL and how these studies targeted PL domains. We conducted a literature search in November 2020 in a total of 18 databases (e.g., Scopus, PubMed, PsycINFO). Eligible studies included those that were either based on or inspired by PL theory; published in academic journals or book sections; and written in English. Synthetic article formats, theses, conference abstracts, and naturalistic interventions were excluded. To explore the link between intervention content and PL theory, we utilized 9/19 Items from the Theory Coding Scheme for behavior change techniques (Michie & Prestwich, 2010). A total of N=39 PL interventions met eligibility criteria and were included in the final analysis. We found that while 76.9% of the studies adopted a holistic understanding of PL, only 15 studies (38.5%) targeted all PL domains (motivation and confidence, physical competence, knowledge and understanding). Notably, only five studies made explicit links between the PL domains and intervention techniques. Our findings support the need for intertwining of PL domains within intervention techniques, in order to acknowledge the holistic nature of PL. (PROSPERO registration: CRD42020188926) <